Winning Arguments from Aristotle to Obama everything you need to know about the art of persuasion - Heinrichs, Jay. (London Penguin, 2007)
Everyone is always trying to persuade us of something: politicians, advertising, the media, and most definitely our families. With all the wisdom of the ages, from Aristotle and Stalin to Yoda and Monty Python, Winning Arguments will show you how to win more than your fair share of arguments, as well as
Includes index
Keywords: Persuasion